Formation of amorphous phase with crystalline globules in Fe–Cu–Si–B and Fe–Cu–Zr–B immiscible alloys. (June 2015) - Nagase, Takeshi; Suzuki, Masanori; Tanaka, Toshihiro
Abstract: The microstructure of rapidly solidified melt-spun ribbons of (Fe0.75 M0.10 B0.15 )100− x Cu x (M = Si, Zr) alloys was investigated focusing on amorphous-phase formation and the solidification structure. In this study, Fe–Cu–Si–B and Fe–Cu–Zr–B alloys were designed to show amorphous-phase formation and liquid-phase separation simultaneously. Amorphous-phase formation was confirmed in both Fe–Cu–Si–B and Fe–Cu–Zr–B alloys. Minor exceptions in a combination map of mixing enthalpy and quaternary predicted phase diagram are acceptable range for designing a quaternary Fe–Cu-based alloy system that shows liquid-phase separation in Fe-based and Cu-based liquids and the formation of an Fe-based amorphous phase. Graphical abstract: Highlights: A prediction way for Fe-Cu immiscible alloys with an amorphous phase was discussed. Amorphous-phase formation is seen in (Fe0.75 M0.10 B0.15 )100− x Cu x (M = Si, Zr) alloys. Liquid-phase separation in Fe–Si–B–Cu alloys realizes an emulsion-type structure.